Analisis Data Pemantauan Kualitas Udara Menggunakan Perangkat Berbasis Arduino Uno dengan Sensor MQ-135 - Patricia Varel De Sanctis (Journal of Computation Physics and Earth Science (JoCPES), 2022)
Air quality is a critical factor that affects human health and the environment. Declining air quality, especially in urban areas, often results from increased pollution caused by transportation, industrial, and domestic activities. A real-time air quality monitoring system based on microcontrollers, such as the Arduino Uno, can be an economical and easily implemented solution [1]. This study aims to design and develop an air quality monitoring device using the Arduino Uno and the MQ-135 gas sensor. The MQ-135 sensor can detect various harmful gases, including carbon dioxide (CO₂), ammonia (NH₃), and sulfur dioxide (SO₂), which are common indicators of air quality. Data from the sensor are collected by the Arduino and displayed on an LCD screen, while remote access is facilitated through a mobile application [2]. This device provides real-time air quality information, helping communities reduce exposure to harmful pollutants. According to the literature, microcontroller- based monitoring systems with gas sensors like the MQ- 135 have proven effective and accurate for detecting air pollution in various environments. This study demonstrates that an Arduino-based air quality monitoring device can offer a practical solution for local air pollution monitoring.